A civil hero : Expert Francisco Pascasio Moreno - Fasano, Héctor L. (2006)
On the May 31, 2002, in commemoration of the 150th anniversary of the birth of Expert Moreno, the distinguished founder of La Plata Museum, we presented tke book Perito Francisco Pascasio Moreno - Un Héroe Civil written by Dr. Héctor L. Fasano. Since then three editions have been published to satisfy the need for a detailed account of Moreno's life and work. He was an outstanding man who gave everytking for his country. Patagonia became one of his principal objectives in life to which he devoted most of his efforts, exploring it continuously for almost 50 years. From 1896 to 1903, Moreno acted as Argentine “perito” (Spanish for “official expert”) in the boundary dispute with Chile. In 1899 he moved to London where he stayed until 1903 and worked as the geographical advisor to the Argentine delegation. In 1899, invited by the Royal Geographical Society, he gave a two-day conference in London which greatly impressed the British scientific community. During these meetings, 65 photographs he had taken in the Andes, in the Argentine Patagonia were shown. This increased the interest to visit and discover what was then considered a mysterious land. The Royal Geographical Society honored Moreno with the title of “honorary member”. Today we proudly offer this book to the foreign visitor and the English-speaking world. Its publication has been made possible througk the sponsorship of the National Tourist Secretariat. Executive Committee of La Plata Museum Foundation